2013
DOI: 10.1136/jech-2013-202614
|View full text |Cite
|
Sign up to set email alerts
|

Geographic access to mammography screening centre and participation of women in the Quebec Breast Cancer Screening Programme

Abstract: Distance affects participation and this effect varies according to rural-urban classification. The lower participation in Montreal Island, where all women lived <12.5 km from a DSC, argues for a major impact of other characteristics or other dimensions of accessibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 24 publications
7
35
0
1
Order By: Relevance
“…The distance decay effect is where levels of health services usage decreases as distance from the actual location of the healthcare facility increases. Previous research has found that distance is an important factor in determining health services utilisation 20 21. As the distance decay effect is primarily an expression of healthcare utilisation, it cannot be interpreted as an indicator of healthcare need, so caution needs to be taken when interpreting our study findings, which have shown that self-harm rates are most elevated in areas that have the shortest travel time to hospital services.…”
Section: Discussionmentioning
confidence: 78%
“…The distance decay effect is where levels of health services usage decreases as distance from the actual location of the healthcare facility increases. Previous research has found that distance is an important factor in determining health services utilisation 20 21. As the distance decay effect is primarily an expression of healthcare utilisation, it cannot be interpreted as an indicator of healthcare need, so caution needs to be taken when interpreting our study findings, which have shown that self-harm rates are most elevated in areas that have the shortest travel time to hospital services.…”
Section: Discussionmentioning
confidence: 78%
“…In order to develop effective promotion strategies, it is essential to identify the modifiable predictors of participation in screening. In the area of cancer screenings, various determinants of screening behaviors have been identified . Based on identified determinants, previous intervention studies have also succeeded in promoting cancer‐screening behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that people who live a short distance from a screening facility were more likely to participate in cancer screening [35]. In addition, people who underwent screening by a primary care physician or a gynecologist during the previous 12 months and people who had many health care visits were also likely to participate in cancer screening [35,36,39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the participation rates in cancer screening were different depending on whether the person eligible for screening lived in an urban area [3,28,34–36]. The interaction terms of four strategies and a binary variable to show whether the municipality was urban (a city or the 23 wards of Tokyo) were included in independent variables of Model 2, while the interaction terms were not included in those of Model 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation